MAT133: Pre Calculus - UiTM, College of Computing, Informatics and Mathematics (2023)
Calculus is a main component in learning mathematics. This subject covers the additional algebraic and trigonometric skills needed by the students before they venture into the world of calculus. It consists of four major parts: coordinates, graphs and lines; functions; systems of equations and inequalities; and trigonometry.